Risk management strategy for the problem of borrowing money for Islamic commercial banks - M. Rif'an Syadali; Segaf Segaf; Parmujianto Parmujianto (Institute of Computer Science (IOCS), 2023)
Despite the fact that Islamic banking has developed significantly over the years, corporate and financial institution risks cannot be separated. There is always a risk when Islamic banks act as financial intermediaries for Indonesian companies. Risk management helps you measure and mitigate risks and find solutions to problems. Bank Syariah Indonesia shows good progress in implementing risk management. The implementation of risk management is generally categorized into eight areas: credit risk, liquidity risk, market risk, operational risk, legal risk, compliance risk, reputation risk and strategic risk. A good implementation of risk management looks like this: Internal control processes and risk management processes must be checked during risk management. Therefore banks need to identify and manage risk management which is part of any banking system. Islamic banks are always faced with risks associated with various and complex transactions.